Wykorzystanie metody Doolittle'a do analizy regresji związku rozwoju ekonomicznego i demograficznego jednostek przestrzennych - Roeske-Słomka, Iwona (Wydział Prawa i Administracji UAM, 1978)
The purpose of the article is an attempt to present using some statistic-mathematical methods in an examination of the influence of economic development on demographic development. The empirical verification concerns the federal countries of the German Federal Republic. Examination and evaluation of the interdependence relation has been accomplished with the aid of the multiple regression analysis and of the variance analysis. For the examination the product values for a worker and for an inhabitant were chosen from general measures of economic development of spatial units. From detailed measures the percentage indicator of households with monthly income of 1,500 DM and more to percentage of marriages lasting less than 6 years was chosen. As the characteristics of procreation processes of population coefficients of general and of group fertilities have been of service. A two-year delay of fertility coefficients in relation to the measures of economic development has been adopted in calculations. To estimate the multiple regression coefficients the Doolittle's method has been used. Following regression equations have been calculated: — for general fertility coefficients — for group fertility coefficients The obtained results suggest that — after reaching a relatively high living standard — the subsequent increase in welfare influences the birth increase except the youngest couples. In their case increase in economic standard causes intensification of actions of competitive elements against possessing and extending the number of children. Values of multiple correlation coefficients were: It appears from the evaluation of importance of the regression equations with the aid of F-test, that economic factors describe in a better way the changes in group fertility than in general fertility.
Utilization of the Doolittle's Method in the Regression Analysis of Economic and Demographic Development of Spatial Units